Will More Diversified Staffs Diversify Newspaper Content? A Pilot Study - Fedler, Fred. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
A pilot study asked 94 students enrolled in introductory newswriting classes at three separate universities to evaluate 18 news stories. About half the stories concerned topics that proponents of multiculturalism have suggested would receive more emphasis if newspapers employed more women and minorities: topics such as breast cancer, divorce, abandoned babies, interracial marriages, abortions, day care, disabilities, welfare, and a contest considered racist and sexist. Using scales from "1" to "10," the students were asked to rate each story's importance, and also to indicate how likely they would be to publish it. Conclusive judgments are not possible given the limited sampling but results are suggestive nevertheless. In many cases, minorities and women did appraise differently the importance of stories and the likelihood that they would use them in the paper and play them on Page 1. Occasionally, the stories that they differed on were not overtly race or gender related, further suggesting that they were making news judgments based on a different set of life experiences. Also, this study indicated that news-ed majors differ from other communication students in their judgments about the importance of various news items. To follow up the implications of this research, similar studies should be conducted with larger samplings of professional news people and general readers. (Contains 24 notes, a listing of the 18 stories used in the study, and nine tables showing results.) (TB)
ERIC Note: Paper presented at the Annual Meeting of the Association for Education in Journalism and Mass Communication (77th, Atlanta, GA, August 10-13, 1994).
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Measures; Cultural Pluralism; Females; Feminism; Journalism; Media Research; Minority Groups; Newspapers; Undergraduate Students; News Stories -- Professional Concerns; Journalism Research; Reports, Research; Speeches/Meeting Papers